Underwater noise in the Slovenian Sea - Popit, Andreja (RMZ-materials and geoenvironment, 2020)
Continuous underwater noise has been monitored in the Slovenian sea near the lighthouse foundation at Debeli Rtič since February 2015, according to the EU Marine Strategy Framework Directive (MSFD). Anthropogenic noise sources (e.g. seawater densities, dredging activities and cleaning of the seafloor) and meteorological noise sources (e.g. wind speed and precipitation) were analysed in relation to the measured underwater noise levels using several graphical and statistical methods. The results of this study showed that average equivalent continuous underwater noise levels were, by 11 dB (Leq,63 Hz) and 5 dB (Leq,125 Hz), higher in the intervals when dredging activities took place than in the intervals when these activities were absent. Variation in underwater noise levels was partly related to the variation of the ship densities, which could be explained by the relatively small acoustic propagation in the shallow seawater. Precipitation level did not indicate any significant association with the variations in continuous underwater noise levels, though some larger deviations in the wind speed were found to be associated with the larger fluctuations in continuous underwater noise levels.
Keywords: measuring equipment; merilna oprema; naravni in antropogeni viri zvoka; natural and anthropogenic sound sources; ogrožanje in varstvo hidrosfere; plitvo morje; podvodni hrup; shallow sea; underwater noise; vodno okolje